Efficiency and distribution in contract farming: the case of Indian poultry growers - Ramaswami, Bharat; Birthal, Pratap Singh; Joshi, Pramod Kumar (International Food Policy Research Institute, 2006)
This paper is an empirical analysis of the gains from contract farming in the case of poultry production in the state of Andhra Pradesh in India. The paper finds that contract production is more efficient than noncontract production. The efficiency surplus is largely appropriated by the processor. Despite this, contract growers still gain appreciably from contracting in terms of lower risk and higher expected returns. Improved technology and production practices as well as the way in which the processor selects growers are what make these outcomes possible. In terms of observed and unobserved characteristics, contract growers have relatively poor prospects as independent growers. With contract production, these growers achieve incomes comparable to that of independent growers.